Georgia Public Expenditure and Financial Accountability Performance Assessment Report : City of Batumi - World Bank Group (World Bank, Washington, DC, 2018)
The purpose of this PEFA assessment is to provide an objective analysis of the present performance of the PFM system in the City of Batumi against the PEFA indicators. This PEFA provides an assessment of PFM in the municipality and establishes a PEFA baseline using the 2016 PEFA methodology. The assessment covered expenditures by subnational government budgetary units. Revenues are collected by the Georgia Revenue Services on behalf of the municipality and this was considered not applicable. There are no extra-budgetary units and no local government below the municipality level. The assessment team visited the municipality from June 5 to 9, 2018 (fieldwork for the assessment). The financial years covered for indicators that required assessing over three years are 2015 to 2017. Overall, the results of the PEFA show that public financial management systems in the City of Batumi are strong and improved as the PFM Reform Action Plan has been implemented. The aggregate expenditure side of the budget performs largely according to plan. The Georgian Treasury consolidates cash balances in the treasury single account on a daily basis. A cash flow forecast is prepared annually for the year to come and is updated quarterly on the basis of actual inflows and outflows often due to relatively frequent supplementary budget. Budgetary units are able to plan and commit expenditure for one year in advance on the basis of quarterly ceilings, in accordance with the budgeted appropriations and commitment releases. An overriding feature of PFM in the Georgia both at the Central and Subnational levels of government has been the development and good use of Information Technology in budget preparation, budget execution (accounts, commitment control, and cash management), personnel and payroll, revenue services, and procurement. The application of the IT has been developed in-country based on business processes in each of the subject areas (redefined as necessary) and not on the reconfiguration of business practices to suit software. This adoption of IT solutions combined with the internet as a vehicle for its implementation by competent and trained personnel (with appropriate control) has been fundamental to the development of strengths in PFM. The integration of IT, internet and personnel has resulted in PFM’s positive effectiveness and efficiency.